2009
DOI: 10.1016/j.rmed.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry, Impulse Oscillometry and Capnovolumetry in welders and healthy male subjects

Abstract: In this study it has been shown that welding associated long-term and short-term effects could be detected in a population of welders, although exposure conditions were quite heterogeneous. The parameters of IOS and Capnovolumetry showed effects even more pronounced than conventional lung function parameters. Thus, these techniques may be considered as an additional tool for occupational medicine research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Additional lung function measurements were taken. The results from this study part were published elsewhere (Gube et al 2009). …”
Section: Methodsmentioning
confidence: 95%
“…Additional lung function measurements were taken. The results from this study part were published elsewhere (Gube et al 2009). …”
Section: Methodsmentioning
confidence: 95%
“…Capnographic measurements can be described by various parameters, and a number of investigations have addressed the question, which of these parameters are suited to assess the presence of airway obstruction (e.g. [8, 11, 12]). One study [10] suggested a high diagnostic accuracy especially for the ratio of slopes of phases 3 and 2 that are obtained when the expiratory CO 2 concentration is plotted against volume (capnovolumetry, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The impulse oscillometry system has been successful, particularly in the respiratory assessment of children, because it does not require effort and it is easy to apply. 4,[5][6][7][8] The literature presents some studies using the impulse oscillometry system as a complementary method of evaluation in children with respiratory disorders, with emphasis on asthma and cystic fibrosis. [8][9][10][11][12] Investigations carried out with healthy children show a growing trend toward determining equations/reference values for new methods of respiratory assessment.…”
Section: Introductionmentioning
confidence: 99%